Design and Characterization of Carboplatin and Paclitaxel Loaded PCL Filaments for 3D Printed Controlled Release Intrauterine Implants - Cem Varan; Davut Aksüt; Murat Şen; Erem Bilensoy (Pharmaceutics, 2023)
Uterine cancer is the fourth most common cancer in women. Despite various chemotherapy approaches, the desired effect has not yet been achieved. The main reason is each patient responds differently to standard treatment protocols. The production of personalized drugs and/or drug-loaded implants is not possible in today’s pharmaceutical industry; 3D printers allow for the rapid and flexible preparation of personalized drug-loaded implants. However, the key point is the preparation of drug-loaded working material such as filament for 3D printers. In this study, two different anticancer (paclitaxel, carboplatin) drug-loaded PCL filaments with a 1.75 mm diameter were prepared with a hot-melt extruder. To optimize the filament for a 3D printer, different PCL Mn, cyclodextrins and different formulation parameters were tried, and a series of characterization studies of filaments were conducted. The encapsulation efficiency, drug release profile and in vitro cell culture studies have shown that 85% of loaded drugs retain their effectiveness, provide a controlled release for 10 days and cause a decrease in cell viability of over 60%. In conclusion, it is possible to prepare optimum dual anticancer drug-loaded filaments for FDM 3D printers. Drug-eluting personalized intra-uterine devices can be designed for the treatment of uterine cancer by using these filaments.